Bayesian adaptive designs for clinical trials - Saville, Benjamin (Henry Stewart Talks, 2016)
Challenges of traditional clinical trial approaches, Adaptive clinical trial characteristics, Examples of adaptive trials, Why use adaptive trials, Drawbacks of adaptive trials, Bodies that need to be involved in adaptive trials, The time is right for adaptive designs, Resources & current applications